Cidade, territórios e cidadania - Marcelo Baumann Burgos (Universidade do Estado do Rio de Janeiro, 2005)
Brazilian cities, and especially the large metropolises, have undergone a process of territorialization, that is, legal and political fragmentation of the urban fabric with the configuration of spaces dominated by informal local authorities. Such spaces take on characteristics common to the favelas (slums) such as those of Rio de Janeiro which have historically displayed this type of ecological configuration. The central hypothesis of this article is that this process of urban territorialization has placed an important constraint on the full exercise of citizenship in low-income areas, since it turns the place of residence into a segregated space, lacking minimum conditions for exercising the most elementary civil rights.